2000
DOI: 10.1121/1.428411
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for subcritical penetration into a sandy bottom: Experimental and modeling results

Abstract: This paper presents preliminary results of a recent study whose overall objectives are to determine the mechanisms contributing significantly to subcritical acoustic penetration into ocean sediments, and to quantify the results for use in sonar performance prediction for the detection of buried objects. In situ acoustic measurements were performed on a sandy bottom whose geoacoustical and geomorphological properties were also measured. A parametric array mounted on a tower moving on a rail was used to insonify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 12 publications
3
52
0
Order By: Relevance
“…However, other measured parameters, e.g., slow wave impedance and speed, slow wave effective This experiment supports the conclusions that subcritical penetration in sandy sediment is from scattering and not from the Biot slow waves [17,26,34]. This is true for two reasons.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…However, other measured parameters, e.g., slow wave impedance and speed, slow wave effective This experiment supports the conclusions that subcritical penetration in sandy sediment is from scattering and not from the Biot slow waves [17,26,34]. This is true for two reasons.…”
Section: Discussionsupporting
confidence: 63%
“…Recent field measurements [17,26,34] have strongly supported the conclusion that subcritical penetration in sands is due to scattering, not Biot slow waves.…”
mentioning
confidence: 87%
“…Maguer et al (2000) present promising sub-bottom detection feasibility even beyond the critical angle in sand using a parametric system. The present study site is characterized by mud having slower sound velocity than the seawater (Richardson and Briggs 1996;Schneider von Deimling et al 2013).…”
Section: Ideal Incidence For Cable Detectionmentioning
confidence: 99%
“…Szender and Kosalos (1997) and Leighton and Evans (2008) presented bistatic (spatially separated acoustic source and receiver) approaches to track underwater cables. Maguer et al (2000) showed experimentally that incidence between of 15°and 30°can be useful for subbottom investigations. Especially for naval mine hunting, sophisticated techniques were developed for enhanced detection of buried targets by towed low-frequency arrays (Jans et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Second, seafloor roughness diffracts energy into the sediment (Thorsos et al, 1997). Third, sediment volume heterogeneity scatters the evanescent wave energy that propagates along the seafloor interface into the sediment (Maguer et al, 2000). In order to compare the predictions of…”
Section: Approachmentioning
confidence: 99%